Big Data and Public Relations. A literature review - Pereira Villazón, Tatiana (2019)
The growing activity generated in digital communication platforms is raising new forms of relationship between organizations and their publics of interest. This has triggered, in turn, the production of a large amount of information, an explosion of data known as Big Data. In this new context, there is a need to study how the management of this huge amount of information faced in public relations, which is constantly generated at high speed and which requires even real-time management. In this work, we present a bibliographic review of the current state of research on the management of Big Data in Public Relations. The results showed a total 41 works. A content analysis of these works found that the activities of internal communications, media relations, crisis communications and issues management are the most related to massive data management.